Auditoría de gestión al Front Operativo del banco pichincha agencia valencia, año 2014 - Barragán Loayza, Lisbeth Isabel (2016)
This research work on the theme: Auditing the Front Operating Banco Pichincha Valencia Agency, 2014, located in the province of Canton Rios Valencia with the aim of developing a management audit processes of Front Operating through an examination can give a clear opinion to management, revealing some inconsistency arises. The most relevant methodology used for this research is exploratory through an examination could obtain reliable information, which allowed us to know the problems in the institution. The design of the experimental research is based on the search for the solution which will indicate the best alternative solutions, the methods used were the observation was applied to personally ensure the facts surrounding the area, the inductive helped develop the interview questions, deductive for the analysis of interviews and analytical allowed to know more the object of study, the techniques used were direct observation, questionnaire and interview applied it to gather the information needed for the report audit. This research project allowed us to obtain the following results in excessive clearance xpertas cards with a moderate risk of 42%, it indicates that you are not making proper management to deliver enablers, which does not fulfill the objectives the agency; the following finding corresponds to the inadequate opening of the agency presents a low risk level of 20% affects the security agency not to make requests to times of keys to each delegate Front Operating which must be requested from the Comand Center; Inconsistencies visa system accounts on this finding presents a low risk level of 40% this affects not to notify inconsistencies to the Managing agency to perform the respective regularization.